Large projected reductions in marine fish biomass for Kenya and Tanzania in the absence of climate mitigation. (1st December 2021) - Wilson, Robert J.; Sailley, Sévrine F.; Jacobs, Zoe L.; Kamau, Joseph; Mgeleka, Said; Okemwa, Gladys M.; Omukoto, Johnstone O.; Osuka, Kennedy E.; Samoilys, Melita; Sauer, Warwick; Silas, Mathew Ogalo; Sululu, Joseph S.; et al.
Abstract: Climate change is projected to cause significant reductions in global fisheries catch during the 21st Century. Yet, little is understood of climate change impacts on tropical fisheries, which support many livelihoods, as is the case in the Western Indian Ocean region (WIO). Here, we focus on two central WIO countries ― Kenya and Tanzania ― and run a multi-species fish model (Size Spectrum Dynamic Bio-climate Envelope Model; SS-DBEM) for 43 species of commercial and artisanal importance, to investigate the effects of climate change. We include both national Exclusive Economic Zones (EEZs) as domains. The model was forced by data from a biogeochemical model (NEMO-MEDUSA), run under the high emissions scenario Representative Concentration Pathway (RCP) 8.5, until the end of the 21st century. Impacts of fisheries and climate change were investigated by running SS-DBEM under five scenarios of fishing pressures to predict a range of possible future scenarios. Fishing pressure was represented as the Maximum Sustainable Yield (MSY), expressed as MSY0, MSY1, MSY2, MSY3 and MSY4 representing fishing mortality of 0, 1, 2, 3 and 4 times MSY, respectively. Large reductions in average fish biomass were projected over the 21st Century, with median reductions of fish species biomass of 63–76% and 56–69% for the Kenyan and Tanzanian EEZs respectively across the fishing scenarios. Tunas were particularly impacted by future climate change, with the six modelled species exhibiting biomass reductions of at least 70% in both EEZs for all fishing scenarios during the 21st Century. Reductions in fish biomass were much more severe during the second half of the 21st Century, highlighting the benefits to tropical fisheries of global action on climate change. Graphical abstract: Image 1 Highlights: Projection of impact of climate change (under RCP8.5) on 43 key species. Focus on two central WIO countries: Kenya and Tanzania. Large reductions in average fish biomass with median reductions of up to 76%. Reductions in fish biomass more severe during the second half of the 21st Century.